Colton nursery hideout - Nussio, Dana (Harlequin romantic suspense, 2021)
"Travis Colton finds that a passionate night with his co-CEO, Tatiana Davison, rocks his world. Not long after, his life changes further when Tatiana confides her pregnancy...and the fact her life is in danger! To the surprise of relationship-averse Travis, he quickly develops undeniable feelings for the family he must keep safe. But when a stalker homes in, Travis must risk it all."--Back cover.